A STUDY OF IMPACT OF DAMS ON BIODIVERSITY (International Journal of Food and Nutritional Sciences, 2022)
Dams alter the ecosystems and biodiversity of rivers. In the old industrialized countries, development now is towards the decommissioning of dams rather than the construction of new ones, but in many developing countries exploitation of rivers is proceeding at a fast rate.